Taming uncertainty - Hertwig, Ralph; Pleskac, Timothy J.; Pachur, Thorsten (Cambridge : MIT Press, 2019)
An examination of the cognitive tools that the mind uses to grapple with uncertainty in the real world.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Uncertainty; Decision making -- Psychological aspects; COGNITIVE SCIENCES/General; ECONOMICS/General